ETHNOMATHEMATICS IN SASAKNESE ARCHITECTURE - Sri Supiyati; Farida Hanum; Jailani Jailani (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2019)
This research is aimed to explore the cultural elements especially in Sasak architectures in Lombok Island such as a home living (Bale), worship building (masjid), lumbung (sambi) in ethnomathematics point of view. This research uses qualitative approach with cognitive (anthropology cognitive). The interviewees are the experienced custom leader and humanists who has conducted the research on Sasak society. Meanwhile, the data collection method used the participant, observation and documentation. Data analysis on this research is not only based on the researcher is interpretation but also the idea structure of the society. This research shows the evidence of sensitivity on the use of numbers practiced by Sasak ancestor long time ago in doing the measurement using their anthropometric ability (Ethnomathematics). The architecture products of sasak society also describe that sasak society is more focus on the process than the final products itself which describes the consistency in conducting role and cultural device which control the desire of individual construction.